Hierarchical Multicomponent Electrode with Interlaced Ni(OH)2 Nanoflakes Wrapped Zinc Cobalt Sulfide Nanotube Arrays for Sustainable High‐Performance Supercapacitors. Issue 22 (28th August 2017) - Syed, Junaid Ali; Ma, Jun; Zhu, Baogang; Tang, Shaochun; Meng, Xiangkang
Abstract: High energy density, fast recharging ability, and sustained cycle life are the primary requisite of supercapacitors (SCs); these necessities can be fulfilled by engineering a smart current collector with hierarchical combination of different active materials. This study reports a multicomponent design of hierarchical zinc cobalt sulfide (ZCS) hollow nanotube arrays wrapped with interlaced ultrathin Ni(OH)2 nanoflakes for high‐performance electrodes. The ZCS exhibits a unique pentagonal cross‐section and a rough surface that facilitates the deposition of Ni(OH)2 nanoflakes with a thickness of 7.5 nm. The ZCS/Ni(OH)2 hierarchical electrode exhibits a high specific capacitance of 2156 F g −1 and excellent cyclic stability with 94% retention over 3000 cycles. This is attributed to enhanced redox reactions, the direct growth of arrays on 3D porous foam acting as a "superhighway" for electron transport, and the increased availability of electrochemical active sites provided by the ultrathin Ni(OH)2 flakes that also sustain the stability of the electrode by sacrificing themselves during long charge/discharge cycles. Symmetric SCs are assembled to achieve high energy density of 74.93 W h kg −1 and exhibit superior cyclic stability of 78% retention with 81% coulombic efficiency over 10 000 cycles. Abstract : Hierarchical arrays of zinc cobalt sulfide (ZCS) hollow nanotubes exhibiting a well‐defined pentagonal cross‐section wrapped with interlaced ultrathin (7.5 nm) Ni(OH)2 nanoflakes are synthesized. The well‐designed nanoarchitecture allows the ZCS/Ni(OH)2 electrodes to achieve high specific capacitances, good rate capability, and excellent cycling stability. An assembled symmetric supercapacitors (SC) delivers higher energy densities than most of the previously reported asymmetric SCs.